An expert patient program to improve the empowerment and quality of life of people with multiple sclerosis: protocol for a multicenter pre-post intervention study - Miguel Angel Robles-Sanchez; Miguel Angel Robles-Sanchez; Miguel Angel Robles-Sanchez; Paloma Amil-Bujan; Cristina Bosch-Farré; Clàudia Coll-Martínez; Clàudia Coll-Martínez; Maria Jesús Arévalo; Elisenda Anglada; Rebeca Menéndez; Xavier Montalban; Jaume Sastre-Garriga; et al. (Frontiers in Neurology, 2023)
IntroductionMultiple sclerosis (MS) causes a progressive disability, which substantially impacts the quality of life (QoL). Health interventions that meet the needs and demands of people with MS are essential to minimize QoL impairment. Expert patient programs (EPPs) facilitate health-related empowerment through peer learning. Based on a previous focus group study, we designed an EPP for MS coordinated by nursing professionals for implementation in the different MS reference units of Catalonia (Southwestern Europe). This study aims to evaluate the effects on quality of life, disease-related knowledge, and self-management related to the health process of the participants of the Expert Patient Program Catalonia™ for people with multiple sclerosis (EPPC-MS).MethodsPre-post intervention multicenter clinical study involving 12 groups of 12 participants: six groups including relapsing and six groups including progressive MS patients, with 144 participants from 7 MS reference units from all over Catalonia, organized in six teams. The intervention will consist of nine telematic learning peer-led sessions (one weekly session). The expert patient (EP) leading the sessions will be an individual with MS with disease-related knowledge, who will be further trained by nurses to lead the sessions. Study variables will be measured before and immediately after the intervention and 6 and 12 months after the end of the sessions and will include: QoL, emotional impact, activation of the person, MS-related knowledge, fatigue, habits and lifestyles, health services use, and program-related experience. Baseline characteristics considered will be sociodemographic data, date of MS diagnosis and type, family history, and treatment characteristics. Variables related to disease follow-up will be new relapses and characteristics and changes in the ongoing treatment. The number of sessions attended will also be collected. Study variables will be analyzed using a pre-post comparison.DiscussionPeer-led learning programs led by EP help empower people with chronic conditions and offer them tools to improve their autonomy and QoL. This study’s intervention will be performed remotely, offering advantages both for people with chronic conditions and the healthcare system regarding the facilitation of family and work conciliation, saving time, simplifying attendance to meetings, lowering costs, and using fewer material resources.Trial registrationNCT04988880 on September 22, 2021.